2010
DOI: 10.1093/geronb/gbq020
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Loss, Children, and the Risk of Nursing Home Admission

Abstract: Overall, 438 (20.7%) husbands and 382 (18.1%) wives were institutionalized, and 362 (17.1%) husbands and 701 (33.1%) wives lost their spouse. Accounting for measured covariates, the risk of nursing home entry doubled for men following spousal death, but was unchanged for women. Results indicate that adult children reduced wives' risk of nursing home admission regardless of husbands' vital status, but buffered husbands' risk only after the death of their wives. We uncover suggestive evidence of parent-child gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 31 publications
2
54
1
3
Order By: Relevance
“…In addition, a spouse can stimulate positive health behaviors [36]. It is suggested that a male spouse may not be as effective as a caregiver for women [37], which makes men more dependent on their woman and women more dependent on a caregiver, because their husband has already died. Our findings must be interpreted in the light of some possible limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a spouse can stimulate positive health behaviors [36]. It is suggested that a male spouse may not be as effective as a caregiver for women [37], which makes men more dependent on their woman and women more dependent on a caregiver, because their husband has already died. Our findings must be interpreted in the light of some possible limitations.…”
Section: Discussionmentioning
confidence: 99%
“…De hecho, el tamaño medio de la red social de los/as usuarios/as de este servicio es menor que el de la población de personas mayores en general (Fernández del Valle y García, 1994) y gran parte de quienes lo utilizan se encuentran en una situación de riesgo social (Serrano y Tena-Dávila, 2004). El apoyo social es, también, una variable crítica en el uso de residencias (Calvete, 1994;Friedman et al, 2006;Luppa et al, 2010;Noël-Miller, 2010), siendo la calidad de la relación con los/as cuidadores/as un factor especialmente determinante para la institucionalización.…”
Section: Discussionunclassified
“…Factores sociodemográficos: ser mujer, carecer de cónyuge, no tener hijos, tener una edad avanzada (Luppa et al, 2010), ser de raza blanca (frente a hispano o afroamericano) y tener un nivel socioeconómico bajo (IMSERSO, 2015;Lee et al, 2001;Lim, 2009;Noël-Miller, 2010 (Buys et al, 2013), y la presencia de deterioro cognitivo y demencia (Tomiak et al, 2000;Gaugler, Kane, Kane, Clay y Newcomer, 2003;Barucha et al, 2004;Damián et al, 2004;McCallum, Simons, Simons y Friedlander, 2005;Sabartés et al, 2009;Lim, 2009;;Lekuona y Calvo, 2010;Cohen-Mansfield y Wirtz, 2011;Maxwell et al, 2013;Almomani et al, 2014;Helvik et al, 2014) Gaugler et al, 2003;Ander, Hyer y Slack, 2007). A su vez, su probabilidad ingreso se incrementa cuando presentan problemas de conducta (Gaugler et al, 2000).…”
Section: Residencias (R)unclassified
“…También se ha observado que compartir el hogar con descendientes beneficia más a las personas mayores no casadas que a las casadas (Speare y Avery, 1993) y que las viudas son más propensas a vivir con descendientes no casados que con casados, si tienen que recibir cuidados (Seltzer y Friedman, 2014). El apoyo filial es determinante para evitar la institucionalización de las personas mayores dependientes, máxime si están viudas (Noël-Miller, 2010), y suele interpretarse en el marco de una solidaridad recíproca a lo largo del curso vital (Bucx, van Wel y Knijn, 2012). b) Otros autores han cuestionado que la convivencia intergeneracional responda a la dependencia parental, ya que primarían en ella, mucho más, las necesidades de los hijos adultos.…”
Section: Alcance De La Convivencia Intergeneracionalunclassified
“…The widowed are also more likely to live with their unmarried descendants than with those who are married if they are in need of care (Seltzer and Friedman, 2014). Support from their children is decisive for avoiding the institutionalisation of elderly persons who are dependent, even more so if they are widowed (Noël-Miller, 2010); this tends to be understood within a framework of reciprocal solidarity existing over the course of the life-cycle (Bucx, van Wel and Knijn, 2012). b) Other authors have questioned the idea that intergenerational co-residence is a response to parental dependency, as what appears to be more important are the needs of the adult children.…”
Section: The Scope Of Intergenerational Co-residencementioning
confidence: 99%